Investigation of heat transfer in tandem and staggered arrangement of wires on single layer wire-on-tube condensers in cross-flow - Gonul, Alisan; Agra, Ozden (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Nowadays, wire-on-tube condensers, especially in industrial applications, are used in forced convection conditions. The effect of tandem and staggered arrangement of the wires welded to the front and back surfaces of the tube in single layer wire-on-tube condensers in cross-flow is investigated in this study. The experimental study is carried out on two different coils, one of which is tandem and the other is staggered. CFD studies are performed according to the related experimental parameters and the results have been observed to be very close to each other. Then, the effect of wire diameter (D-w), tube diameter (D-t), wire spacing (S-w), tube spacing (S-t), staggering rate (S-s) and free stream velocity (U-f) on heat transfer is examined parametrically for wide ranges. Furthermore, the variation of the convective heat transfer coefficients on the wire (h(w)) and the tube (h(t)) are investigated by Genetic Aggregation Response Surface Method (RSM) according to the geometric parameters. Sensitivity analysis of the parameters affecting h(w), and h(t) is performed by means of this method. As a result of the study, it is determined that the wires in the back row in the direction of flow in the tandem arrangement is dominantly under the influence of the wires in the front row. A decrease in heat transfer is observed because of this situation. This effect is largely eliminated by the staggered arrangement of the wires. The heat transfer coefficient on the wires is improved around 18-22% by increasing the value of staggering rates from 0 to 0.25. It is determined that the variation of staggered rate values slightly affects h(t). Free stream velocity is found to be the most effective parameter in terms of heat transfer via the sensitivity analysis. Also, it is concluded that S s is the most effective parameter on h is , among the geometric parameters studied. Over 700 analyzes have been performed according to different combinations of 1.20 mm <= D-w <= 2.00 mm, 2.1 <= D-t/ D-w <= 8.64, 1.75 <= S-w/D-w <= 8.33, 2.0 <= S-t/D-t <= 11.90 mm intervals and 0.5 <= U-f <= 2.5 m/s free stream velocity. This data is compared via three correlations in the literature to estimate the convective heat transfer coefficient on the wire and the tube respectively. A correction factor has been added to Gonfil et al.'s (2020) correlation [1] that takes into account the staggering effect for the calculation of convective heat transfer coefficient on the wire (h(w)). Thus, h(w), gives results in the 10% error range when compared with the CFD analysis results. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Forced convection; Wire-on-tube condenser; Staggered arrangement; Tandem arrangement; NUMERICAL-SIMULATION; FORCED-CONVECTION; RESPONSE-SURFACE; 2 CYLINDERS; FLUID-FLOW; OPTIMIZATION; EXCHANGER; PERFORMANCE; BANKS; CFD; Thermodynamics; Engineering; Mechanics